Airway Obstruction: A Comprehensive Literature Review on Etiology, Pathophysiology, and Clinical Management - Diska Aprisa Lestari; Rika Yolanda Putri; Baiq Rizqika; Muhammad Sultan (International Journal of Public Health Excellence (IJPHE), 2026)
Airway obstruction represents a critical medical condition characterized by narrowing or complete blockage of the respiratory passages, leading to impaired ventilation and potentially life-threatening complications. This comprehensive literature review examines the multifaceted aspects of airway obstruction, encompassing its definition, classification, epidemiology, pathophysiology, clinical manifestations, diagnostic approaches, and management strategies. Airway obstruction can be categorized based on duration (acute vs. chronic), anatomical location (upper vs. lower respiratory tract), and severity (partial vs. complete obstruction). The global burden of this condition is substantial, with chronic obstructive pulmonary disease (COPD) affecting approximately 391.9 million individuals worldwide, asthma impacting 262 million people, and acute lower respiratory infections contributing significantly to morbidity and mortality, particularly in pediatric populations. The pathophysiology involves complex interactions between anatomical factors, inflammatory responses, smooth muscle dysfunction, and structural remodeling. Clinical presentation varies according to obstruction location and severity, ranging from wheezing and stridor to respiratory failure and cardiac arrest. Diagnostic evaluation requires systematic physical examination, careful history taking, and appropriate imaging modalities including radiography, CT scanning, MRI, and bronchoscopy. Management strategies encompass both pharmacological interventions (bronchodilators, corticosteroids, epinephrine, antibiotics) and non-pharmacological approaches (chest physiotherapy, breathing exercises, positional therapy). Early recognition and prompt intervention remain paramount in preventing fatal complications. This review synthesizes current evidence to provide a comprehensive understanding of airway obstruction, emphasizing the importance of timely diagnosis and individualized management approaches